A hybrid method (MVMO+TSM) for the parameter estimation of one-axis generators model - Medina Vigoria, Edsson Frank (2023)
Descargue el texto completo del repositorio institucional de la Universidade de São Paulo: https://doi.org/10.11606/D.18.2023.tde-14062023-095148